Development of a novel judo-specific Ippon reactive agility test: a reliability and validity study - Tascan, M. B.; Akkus, C.; Turgut, E. (The Journal of Strength and Conditioning Research, 2025)
Agility is a critical component of performance in judo, yet no valid and reliable test specifically assesses reactive agility in judokas. The primary aim of this cross-sectional study was to develop and validate a novel reactive agility test for judokas and to examine its test-retest reliability, validity, and discriminative validity. Thirty-four male judokas were recruited from the National Judo Team. The Ippon Reactive Agility Test (IpponRAT) was developed and evaluated in 3 stages, with its feasibility being assessed. The test measured key performance components, including movement time (MT), reaction time (RT), and decision-making time (DT). To assess test-retest reliability, subjects completed the IpponRAT in 2 separate sessions. To assess validity, its correlation with Special Judo Fitness Test (SJFT) was evaluated. Discriminative validity was evaluated by determining whether the test could discriminate judokas based on their competition level. The IpponRAT demonstrated high test-retest reliability for MT (intraclass correlation coefficient [ICC] = 0.82), and good reliability for RT (ICC = 0.71), but poor reliability for DT (ICC = 0.36). The IpponRAT MT showed a high correlation with the SJFT (r = 0.62, p < 0.001), whereas the IpponRAT DT showed a moderate correlation (r = 0.34, p < 0.05). The test discriminated athletes based on their competition level, indicating strong discriminative validity (area under the curve >0.7, p < 0.05). The IpponRAT is a novel judo-specific reactive agility test that is feasible, reliable, and valid. The IpponRAT can be recommended for monitoring reactive agility performance, assessing return-to-sport readiness, and evaluating injury risk in judokas.